8b+6=-9+3b

Simple and best practice solution for 8b+6=-9+3b equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8b+6=-9+3b equation:


Simplifying
8b + 6 = -9 + 3b

Reorder the terms:
6 + 8b = -9 + 3b

Solving
6 + 8b = -9 + 3b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-3b' to each side of the equation.
6 + 8b + -3b = -9 + 3b + -3b

Combine like terms: 8b + -3b = 5b
6 + 5b = -9 + 3b + -3b

Combine like terms: 3b + -3b = 0
6 + 5b = -9 + 0
6 + 5b = -9

Add '-6' to each side of the equation.
6 + -6 + 5b = -9 + -6

Combine like terms: 6 + -6 = 0
0 + 5b = -9 + -6
5b = -9 + -6

Combine like terms: -9 + -6 = -15
5b = -15

Divide each side by '5'.
b = -3

Simplifying
b = -3

See similar equations:

| 32-6b-5b=7.25 | | 3+3x=x-3 | | 1+7r=-7+3r | | 2(5x-1)=3x(x+1) | | 8x-2=-7+7x | | 2x+8=-5 | | -107=3-10x | | 7n+3=-67 | | 7=6-v | | 5c-3-4c=2c+2 | | 160+(16x+32)=180 | | 3a=1 | | (3x-4)(x^2-5x+1)= | | -9x^2+5x+12=0 | | 6(2a^2+3a)=18-12a | | 4x-18+4x=180 | | 15-(2m+4)=4+2m-13 | | -3y(6y+7)= | | 6x-20=4x+40 | | 7.34*1.8= | | 3+6x=-4y | | 7x^2-4x+.5717285714=0 | | -8r-4=7r-4 | | 8x^2+9x+6.5=0 | | x^2+3.81x+3.61=0 | | 2.5d=40+50 | | .2(d-6)=.3d+5-3+.1d | | x^2+2.40x+1.44=0 | | 4x+5=x+32 | | 57.86-9.95= | | 18k^3-48k^2+66k= | | 2.5d=0.4+50 |

Equations solver categories